2019
DOI: 10.35219/foodtechnology.2019.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a microbial pigment obtained from Serratia marcescens as a natural food colourant

Abstract: The use of naturally sourced pigments in the food industry is limited due to their instability when exposed to processes and parameters such as light, pH, and high temperatures. Research has moved towards exploiting pigmented microorganism as sources of potential natural colorants, with the color red representing the largest market segment in the color industry, utilized in various food applications. This study was aimed isolation and characterization of Prodigiosin obtained from Serratia marcescens for potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It has been reported that short chain alcohols modulate the properties of phospholipid bilayers promoting their permeabilization [67,68]. By promoting PG protonation [69,70], the acetic acid component potentially enhances PG binding to the negatively charged LAG membrane via strong electrostatic interaction with head groups of teichoic and lipoteichoiuc acids. Localization of PG in the LAGs cell envelopes was verified by TEM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that short chain alcohols modulate the properties of phospholipid bilayers promoting their permeabilization [67,68]. By promoting PG protonation [69,70], the acetic acid component potentially enhances PG binding to the negatively charged LAG membrane via strong electrostatic interaction with head groups of teichoic and lipoteichoiuc acids. Localization of PG in the LAGs cell envelopes was verified by TEM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A simple incubation method allowed 3.9% loading of LAGs by varying the composition of a methanolacetic acid solvent system, temperature, incubation time and agitation rate. The solvent system had a key role in PG loading as it was shown to promote permeabilization of the bacterial phospholipid bilayer 37,38 and protonation of PG 39,40 . This would enhance PG binding to the negatively charged LAG membrane via strong electrostatic interaction PG loading which was con rmed by digital and microscopic imaging (Fig.…”
Section: Discussionmentioning
confidence: 99%